Developing Character Education Using the Concept of Sekolah Perjumpaan Approach - Sar'in; Rahimah Embong; Nurul Anwar (Institute of Computer Science (IOCS), 2022)
Sekolah Perjumpaan (SP) is a concept that has similarities with the 2013 curriculum but has differences in its implementation. SP emphasizes more on individual moral awareness continuously based on mutually agreed commitments, there are three forms of interaction that cannot be avoided by every human being, namely: (1) human interaction with God (Trans-cognitive), (2) human interaction with others ( Re-Cognitive), and (3) Human interaction with objects (Cognitive). SP emphasizes continuous human interaction with other people in every meeting because character-building students not only talk about the concept of character education but also how to apply it every day. This study aims to determine the implementation of SP in SMA 1 Gunung Sari. In this study, researchers used a qualitative approach. The sample in this study amounted to 15 participants who were selected using the purposive sampling method. Interview and FGD are data collection techniques used in this study. For data analysis, this research applies thematic analysis. The results showed that SP was successfully implemented in SMA 1 Gunung Sari. Based on the results of interviews and FGDs, it was shown that there was a positive change in character for the students of SMA 1 Gunung Sari.